A Ngai Tahu Perspective on Some Treaty Questions - O’Regan, Tipene (Victoria University of Wellington Law Review, 1995)
The author, then the Chairman of the Ngai Tahu Maori Trust Board and of the Treaty of Waitangi Fisheries Commission – Te Ohu Kai Moana, provides a perspective on Treaty issues from the perspective of the Ngai Tahu. The author outlines Ngai Tahu’s engagement in formal proceedings before the Waitangi Tribunal on an extension of the WAI 27 case under the Crown Forest Assets Act 1989, the first such case of its kind to have reached that stage of development. The author concludes that questions regarding the relationship between governance and tino rangatiratanga will be addressed by the Institute of Advanced Legal Studies. *This article also contains a question and answer session with Sir Tipene.